CXC chemokine ligand 12α-mediated increase in insulin secretion and survival of mouse pancreatic islets in response to oxidative stress through modulation of calcium uptake - Vidakovic, Melita; Garrido, Ernesto Caballero; Mihailovic, Mirjana; Arambasic Jovanovic, Jelena; Sinadinovic, Marija; Rajic, Jovana; Uskokovic, Aleksandra; Dinic, Svetlana; Grdovic, Nevena; Djordjevic, Milos; Tolic, Anja; Poznanovic, Goran (Archives of Biological Sciences, 2018)
We examined whether CXCL12α improves insulin secretion by influencing the Ca2+ oscillation pattern and Ca2+ influx ([Ca2+]i), thereby enhancing the viability of pancreatic islet cells in oxidative stress. The islets of Langerhans were isolated from male OF1 mice and pretreated with 40 ng/mL of CXCL12α prior to exposure to 7.5 µM hydrogen peroxide, which served to induce oxidative stress. Incubation of islets with CXCL12α induced pancreatic β-cell proliferation and improved the ability of β-cells to withstand oxidative stress. Consecutive treatments of isolated islets with hydrogen peroxide caused a decline in β-cell functioning over time, while the CXCL12α pretreatment of islets exhibited a physiological response to high glucose that was comparable to control islets. The attenuated response of islets to a high D-glucose challenge was observed as a partial to complete abolishment of [Ca2+]i. Treatments with increasing concentrations of CXCL12α decreased the number of Ca2+ oscillations that lasted longer, thus pointing to an overall increase in [Ca2+]i, which was followed by increased insulin secretion. In addition, treatment of islets with CXCL12α enhanced the transcription rate for insulin and the CXCR4 gene, pointing to the importance of CXCL12/CXCR4 signaling in the regulation of Ca2+ intake and insulin secretion in pancreatic islet cells. We propose that a potential treatment with CXCL12α could help to remove preexisting glucotoxicity and associated temporary β-cell stunning that might be present at the time of diabetes diagnosis in vivo. https://doi.org/10.2298/ABS170711040V Received: July 11, 2017; Revised: October 23, 2017; Accepted: October 24, 2017; Published online: October 30, 2017 How to cite this article: Vidaković M, Garrido EC, Mihailović M, Arambašić-Jovanović J, Sinadinović M, Rajić J, Uskoković A, Dinić S, Grdović N, Đorđević M, Tolić A, Poznanović G. CXC chemokine ligand 12α-mediated increase in insulin secretion and survival of mouse pancreatic islets in response to oxidative stress through modulation of calcium uptake. Arch Biol Sci. 2018;70(1):191-204.